Students’ Emotional Engagement in Learning English Vocabulary through Multimodality of Graffiti Art in ESP Class - Isnaini Eddy Saputro; Abdurrachman Faridi; Mursid Saleh; Frimadhona Syafri (Universitas Negeri Semarang, 2023)
A key to enhance students’ engagement in learning English Vocabulary (LEV) is applying efficient ways to use in teaching process. By using graffiti arts that created by government as the art wall in Sorong are media to engaged students in learning English Vocabulary. The language used in graffiti art is two languages, Indonesia and English and also the contents are about the social issues of health environment occasioning in Sorong City that is suitable used in teaching English vocabulary for students in public health study program. There are 33 students of public health study program in second semester. This research used more than 20 graffiti arts to engage students in LEV. This research used descriptive case study to answer the research question through observation. Observation checklist, Class-related Emotions Questionnaire (CEQ, and Manipulation Check Questions are used as research instrument for data collection. The students of public health program are enjoyable learning English by using graffiti. The students’ emotional engagement are found such as interact with other students and lecturer by vocabulary boosting, asking and answering the questions, giving opinion, explaining, spelling the word, writing the complete sentence, argument to give solution relating to the content social of graffiti.